Synthesis, characterization, electrical and dielectric permittivity measurements of 2,9,16,23-tetra(4-ferrocenylimino-3-nitrophenoxy)phthalocyanines - (:unkn) unknown (SOC PORPHYRINS & PHTHALOCYANINES, 2006)
2,9,16,23-tetra(4-amino-3-nitrophenoxy)phthalocyanines were synthesized from 4-(4-amino-3-nitrophenoxy)phthalonitrile which was obtained from 4-nitro-1,2-dicyanobenzene and 4-amino-3-nitrophenol. 2,9,16,23-tetra(4-ferrocenylimino-3-nitrophenoxy)phthalocyanine and 2,9,16, 23-tetra(4-ferrocenylimino-3-nitrophenoxy)phthalocyaninatocobalt(II) were synthesized in a one-step condensation reaction of ferrocenylaldehyde with 2,9,16,23-tetra(4-amino-3-nitrophenoxy)phthalocyanine and 2,9,16,23-tetra(4-ainino-3-nitrophenoxy)phthalocyaninatocobalt(II), respectively. The novel compounds were characterized by elemental analysis, Inductively Coupled Plasma (ICP-MS), UV-vis, IR and H-1 NMR spectroscopy. The effects of temperature and frequency on the conduction properties (a.c. and d.c.) and the dielectric constant were studied on pellet samples of 2,9,16,23-tetra(4-amino-3-nitrophenoxy)phthalocyanine, 2,9,16,23-tetra(4-ferrocenylimino-3-nitrophenoxy)phthatocyanine, 2,9, 16,23-tetra(4-amino-3-nitrophenoxy)phthalocyaninatocobalt(II) and 2,9,16,23-tetra(4-ferrocenylimino-3-nitrophenoxy)phthalocyaninatocobalt(II), with evaporated, ohmic gold electrodes in the frequency range 40-10(5) Hz. and within the temperature range 290-400 K. Unlike many metallophthalocyanines, a variable-range hopping model is found to most appropriately fit the experimental conductivity data of 2,9,16,23-tetra(4-ferrocenylimino-3-nitrophenoxy)phthalocyanine and 2,9,16,23-tetra(4-ferrocenylimino-3-nitrophenoxy)phthalocyaninatocobalt(II), while for 2,9,16,23-tetra(4-amino-3-nitrophenoxy)phthalocyanine and 2,9,16,23-tetra(4-amino-3-nitrophenoxy)phthalocyaninatocobalt(II), thermally activated conduction with single activation energy is valid. Frequency and temperature dependence of the a.c conductivity were analyzed in terms of existing theory for 2,9,16,23-tetra-(4-amino-3-nitrophenoxy)phthalocyanine, 2,9,16,23-tetra(4-ferrocenylimino-3-nitrophenoxy)phthalocyanine, 2,9,16,23-tetra(4-amino-3-nitrophenoxy)phthalocyaninatocobalt(II) and 2,9,16,23-tetra(4-ferrocenylimino-3-nitrophenoxy)plithalocyaninatocobalt(II). It was found that the a.c. conductivity of the compounds depends on the frequency, obeying the empirical formula, sigma(ac) = A(T)w(s). The model parameters calculated are reasonable and consistent with the prediction of the correlated barrier hopping model for 2,9,16,23-tetra(4-ferrocenylimino-3-nitrophenoxy)phthalocyanine and 2,9,16,23-tetra(4-ferrocenylimino-3-nitrophenoxy)phthalocyaninatocobalt(II) and the quantum mechanical tunneling model for 2,9,16,23-tetra(4amino-3-nitrophenoxy)phthalocyanine and 2,9,16,23-tetra(4-amino-3-nitrophenoxy)phtlialocyaninatocobalt(II). The dielectric constant of the compounds increased with temperature and decreased with frequency in the investigated range. Copyright (c) 2006 Society of Porphyrins & Phthalocyanines.
Keywords: phthalocyanine; ferrocenyl; variable range hopping; dielectric permittivity; PHTHALOCYANINE THIN-FILMS; METAL-FREE; CONDUCTION